Space Vs. Networks in the Geography of Innovation: A European Analysis - Mario A. Maggioni; Mario Nosvelli; T. Erika Uberti (Fondazione Eni Enrico Mattei (FEEM), 2006)
In the last fifteen years, income differences among European Member States have been strongly narrowing while the process has been matched with a widening of the inter-regional variance within single countries. Traditionally, regional economic disparities in Europe have been ascribed to peripherality and/or to a high level of dependence on declining sectors. Nowadays regional disparities can be no longer defined only in terms of statistical differences in the values of standard macroeconomic indicators, but also according to innovative capacities and knowledge endowment. This paper provides an original framework for the interpretation of the existing relationships between innovation process and research activity in Europe and the structural and geographical features shaping the European scientific and technological map. In order to do so, we focus on two knowledge-based relational phenomena: participation in the same research networks (funded by the EU Fifth Framework Programme) and EPO co-patent applications. Using two complementary econometric techniques we try to assess those factors that determine patenting activity, distinguishing structural features, geographical and relational spillovers. Through these variables we measure the intrinsic relational structure of knowledge flows which directly connects people, institutions and, indirectly, regions, across European countries in order to test whether hierarchical relationships based on a-spatial networks between geographically distant excellence centres prevail over diffusive patterns based on spatial contiguity.
Keywords: O31; R12; C21; 330; Spatial Distribution; Networks; European Analysis